The Shift of University Students’ Communication Ethics in Post-COVID-19 Pandemic Learning - Martini, Endang; Yuliarti, Monika Sri; Prakoso, Septyanto Galan; Budiwati, Christiyaningsih (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
The COVID-19 pandemic has left behind a wide range of effects. As a potential future learning paradigm, one of them is the hybrid learning model. In terms of appearance during lectures, whether directly or indirectly through the use of post-COVID-19 pandemic media, this study attempts to characterize the communication ethics of generation Z students at Sebelas Maret University Vocational School in Surakarta. The quantitative descriptive method is thought to be the most appropriate approach to use in addressing the study objectives. Secondary data is derived from internal data in the education sector, publications, books, and other documentation, while primary data is collected online using semi-open questions in addition to observation. It is possible to conclude that there is a lack of good student communication ethics when it comes to appearance during online learning because not all students have turned on their cameras, not all of them are dressed collared, and not all of them follow the dress code that has been established in accordance with previous agreements in a number of courses.